De la demonización al racismo (sobre la deshumanización del otro) - Bello Reguera, Gabriel (2023)
This article initially focuses on the demonization of the other in order to analyze two variants or depictions of the demon: one is mythical, the nourishment of religious- theological discourse, and the other is secularized. In both cases the demon is the representation of evil in itself, in its own makeup or root. The first is analyzed in “Occidentalist” discourse, the image that certain Eastern religious and political circles have of the West, used in their politics of violence, and it is completed by the political role played by demonization. The second is the secularization of the demon, and it was proposed by the French philosopher L. Ferry in order to make sense of episodes of extreme violence that exceeded the limits of common sense, episodes which occurred in the Balkans and in Central Africa in the nineteen nineties. The critique of the secularized version of the devil makes way for another explanation of the evil that was apparent in those episodes; it was offered by the American philosopher R. Rorty. Rorty explains this excessive violence, this evil, through animalization and feminization, two new forms of dehumanization. Finally, the limits of Rorty’s theory allow for a fourth kind of dehumanization that he does not explicitly consider: racism. The article ends by analyzing the basic elements of racism: its political func tion, its theoretical and moral structure, and its historical and philosophical development.